Pemikiran Ali Syari'ati tentang Revolusi dalam Perspektif Filsafat Sosial dan Relevansinya dengan Perubahan Sosial di Indonesia - , MUTIULLAH ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The title of the research is the revolution on Ali Syariâatiâs thought and its relevance for Indonesian social change. This research has explored Ali Syariâatiâs thought of transcendental revolution. The main problem of this research is morality, independent, humanity, social juctice and peace. Indonesian coping with the problems are not enough merely to contemplate, but also it is necessary to move for a change. The spirit to change brings me into transcendent revolutionary discourse pertaining to a revolutionary concept that is not driven by the conflict between classes, as Marx thought, but revolution based on critical consciousness and religion. The purpose of this research is to construct Ali Syariâatiâs thought for Indonesian social change. This research is qualitative on philosophy that was employed to find out, represent and study Ali Syariâatiâs thought at the best. It applied two methods: firstly, hermeneutics, applied to reveal the essentials of three revolutionary foundations: Islamic Theology, existential human being and enlightened intellectuals